Characteristics Of Pregnant Women With Anemia - Ufarah Indah Sari; Masita Fujiko; Mir’atul Ginayah (Jurnal EduHealth, 2024)
Anemia is a condition of decreased hemoglobin levels , hematocrit and erythrocyte count below normal values . Anemia in pregnancy can have harmful effects on the mother and fetus. Iron deficiency anemia (IDA) is most common in pregnancy women . pregnant women are at high risk of IDA because the need for iron increases significantly during pregnancy . pregnant women are said to be anemic if their blood hemoglobin is less than 11%. This literature review aiming to determine the characteristics of pregnant women with anemia from various articles . This study uses a descriptive literature review approach . Article search via Google Scholar , Science Direct , and Pubmed according to keywords are then analyzed according to inclusion and exclusion criteria . The results obtained in this literature has 15 articles with a limit of 2020 - 2024. In this literature review study, the characteristics of maternal age , education , occupation , economic status, place of residence , gestational age , parity , nutritional status, dietary habits and compliance with taking iron tablets affect the incidence of anemia in pregnancy . The incidence anemia in pregnancy is more common in the 20-35 year age group , having low education , low income , living in rural areas areas , multiparous mothers , gestational age in the third trimester of pregnancy , experiencing CED ( Chronic Energy Deficiency ), rare consuming meat , green vegetables , tea habits of consuming tea and coffee after eating , and not complying with taking iron tablets.